ChemInform Abstract: A Facile H2SO4—SiO2‐Catalyzed Ferrier Rearrangement of 3, 4, 6‐Tri‐O‐benzyl‐D‐glucal. Issue 7 (18th February 2014) - Zhang, Jianbo; Zhang, Bo; Zhou, Jiafen; Chen, Heshan; Li, Juan; Yang, Guofang; Wang, Zhongfu; Tang, Jie
Abstract 15 examples